A comprehensive review on microalgae based astaxanthin: bioprocess optimization, technological barriers, industrial applications and future roadmap - Jaryal, Shivangi; Sharma, Amit Kumar; Lamba, Bhawna Yadav; Patel, Alok (Frontiers in Marine Science, 2025)
Astaxanthin, a potent ketocarotenoid of C40 family, has drawn significant attention in food, healthcare and personal care industries due to its exceptional anti-inflammatory, antioxidant, and anti-proliferative properties. Microalgae have recently gained recognition as one of the most promising natural sources for astaxanthin production. However, there are several technical barriers in both the upstream and downstream processes that result in microalgae-derived astaxanthin remaining costly. Hence, this review explores recent trends and advancements in astaxanthin production from microalgae. It provides an in-depth review of the biochemical processes that lead to the accumulation of astaxanthin in microalgal cells, highlighting significant factors that affect production, including environmental factors, strain selection, and bioreactor configuration. Different emerging extraction techniques such as physical, biological, and chemical methods are evaluated based on scalability and efficiency. The diverse applications of astaxanthin, particularly in the food, nutraceutical, and pharmaceutical sectors, are also discussed. Furthermore, the review identifies major scientific and technological challenges, such as low biomass yield and high production costs, which hinder large-scale commercialization. In conclusion, future research directions are proposed to overcome these limitations and promote the development of sustainable, cost-effective, and commercially viable microalgae-based astaxanthin production systems.